Zentralanatolische Toponyme auf °šna und ein hattisches Suffix: Zum ursprünglichen Verbreitungsgebiet des Hattischen - Simon, Zsolt (Altorientalische Forschungen, 2018)
This paper provides a linguistic re-analysis of the toponyms ending in ° šna in Anatolian cuneiform texts. It argues that due to phonological reasons not all of them can be explained with a Hittite suffix as it is usually done and a similar Hattian suffix fits better. The toponyms with the Hattian suffix provide the first evidence that Hattian was once spoken south of the Kızılırmak river. As a by-product, new etymologies for some Hittite words and toponyms as well as an extended Palaic speaking territory are suggested.